BICONTINUOUS CONCENTRIC LAMELLAR SILICA AS A MICRO-REFLECTOR FOR DYE-SENSITIZED SOLAR CELLS AND ITS MODIFICATION FOR PHOTOCATALYSIS - Silmi, Nadiatus
Silica with bicontinuous concentric lamellar (bcl) morphology has many advantages, including open pore structure, large surface area, adjustable particle size, increased pore size and pore volume, along with high mechanical, thermal, and hydrothermal stability. Its unique morphology and open pore structure are very interesting for further study. Therefore, in this research, a quantitative analysis of the morphology and pore structure of bcl silica was carried out easily and simply through SEM (scanning electron microscope) and TEM (transmission electron microscope) image processing. The electron path during SEM imaging was simulated through Monte-Carlo simulation using CASINO software to understand electron microscope imaging better. Next, using ImageJ and MATLAB software, the morphology and pore structure of bcl silica were studied by applying various image processing techniques, including binary image analysis, Shannon entropy, and gray value intensity profiles. The results of qualitative observations of SEM images show that the morphology of bcl silica is spherical with bicontinuous lamellae, and there is an open channel structure between the lamellae. Monte-Carlo simulations show that the density of silica particles affects the diameter of the electron trajectories and will influence the amount of signal detected by the detector. The smaller the density of the silica particles, the larger the release diameter so that the image produced by SEM can include more complete information about the morphology and surface structure of the sample. Due to its unique structure and high porosity, the bcl silica has a relatively low density compared to non-porous silica. Therefore, this simulation can describe variations in topographic contrast in SEM images of bcl silica, namely the presence of lamellae and open channel structure. Variations in topographic contrast in SEM images underlie the lamellae density analysis through binary image quantization. Binary image quantization produces a lamellae cross-sectional area ratio (AL/Atotal). The bcl silica synthesized using the reflux method for 8 hours produces an AL/Atotal value of 50% and a narrowness of the V-groove between lamellae (? angle) of 4.1°. Comparison with silica particles from external publications shows that high lamella density leads to an increase in AL/Atotal and a decrease in ?, while a low lamella density results in a decrease in AL/Atotal and an increase in ?. Furthermore, Shannon entropy can measure the level of complexity of an image. The Shannon entropy considers the randomness of the image pixel intensity distribution. As the reflux time increases, up to 72 hours, the Shannon entropy of the SEM image increases. A higher entropy value indicates a wider grayscale pixel variation. Furthermore, the internal morphology of bcl silica was analyzed through the gray value intensity profile of the TEM image. The intensity profile of the gray values along the particle diameter in the form of a line or overall in the form of a circle shows a high density at the core of the particle and a lower density towards the edge of the particle. The quantitation results further validate the concentric nature and prove the V-shaped pore structure of bcl silica, known as V-groove. The unique morphology of bcl can support silica applications in various fields, including solar cells and photocatalysis. Using bcl silica as a micro-reflector in a dye-sensitized solar cell (DSSC) photoanode can increase efficiency by 16.7%. The results of DSSC performance measurements show that bcl silica is superior to MCM-41 silica because the presence of bcl morphology can increase the refractive index contrast, thereby facilitating an increase in total internal reflection. Simulations using the Bruggeman effective medium approach prove that bcl silica has a lower effective refractive index than non-porous silica and TiO2. Meanwhile, bcl silica is used as catalyst support for ceria (CeO2) and titania (TiO2) in the photocatalysis field. Photocatalytic activity testing was carried out in situ using photoluminescence spectroscopy. Ceria-decorated bcl silica with 8 mmol of cerium(IV) ammonium nitrate loading showed the highest photocatalytic efficiency of 47% within 90 minutes, with a photodegradation rate of 24.9 × 10?3 min?1. This result surpassed pristine ceria with a photocatalytic efficiency of 39% within 90 minutes and a photodegradation rate of 10.7 × 10?3 min?1. In addition, titania decorated bcl silica with a loading of 0.1 mol titanium tetrachloride achieved the highest photocatalytic efficiency of 98% within 47 minutes with a photodegradation rate of 105 × 10?3 min?1. Overall, this study reveals the applicative potential of bcl silica in solar cells and photocatalysis and provides an in-depth understanding of the morphological properties and performance of bcl silica in these applications.